Mengenal Sistim Proporsional Terbuka Di Indonesia Menuju Pemilihan Umum Tahun 2024 - TITONY TANJUNG (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The electoral system in Indonesia has not changed too much because it still uses proportional, starting from a closed proportional system (close list PR) to an open proportional system (open list PR). The phenomenon that occurs in elections with an open proportional system has been carried out since after the amendment to the 1945 Constitution with various regulations issued one after another. Both of these systems raise pros and cons in society. In order to prevent multiple interpretations, it is necessary to have an understanding of the development of a proportional system in legislative elections in Indonesia, what are the advantages and disadvantages of each of these systems, so that people can find out the reasons for choosing the electoral system in Indonesia. At present the debate regarding the 2024 general election system (Election) has re-emerged along with the judicial review of Law Number 7 of 2017 concerning Elections to the Constitutional Court (MK). Considering that the electoral system is an important aspect of holding elections, the 2024 election system that will be used later must be completed as soon as possible. The approach used in this research is normative juridical. Specified as descriptive research, data collection techniques by using literature to obtain secondary data, and data analysis techniques are analytical descriptive